Priming Dendritic Cells for Th2 Polarization: Lessons Learned from Helminths and Implications for Metabolic Disorders - Hussaarts, Leonie; Yazdanbakhsh, Maria; Guigas, Bruno (Frontiers in Immunology, 2014)
Nearly one quarter of the world’s population is infected with helminth parasites. A common feature of helminth infections is the manifestation of a type 2 immune response, characterized by T helper 2 (Th2) cells that mediate anti-helminth immunity. In addition, recent literature described a close association between type 2 immune responses and wound repair, suggesting that a Th2 response may concurrently mediate repair of parasite-induced damage. The molecular mechanisms that govern Th2 responses are poorly understood, although it is clear that dendritic cells (DCs), which are the most efficient antigen-presenting cells in the immune system, play a central role. Here, we review the molecular mechanisms by which DCs polarize Th2 cells, examining both helminth antigens and helminth-mediated tissue damage as Th2-inducing triggers. Finally, we discuss the implication of these findings in the context of metabolic disorders, as recent literature indicates that various aspects of the Th2-associated inflammatory response contribute to metabolic homeostasis.